The present situation of job satisfaction and differences in its influencing factors of general practitioners and specialists in China - WANG Shiqi; JIANG Qingqing; YOU Qiqi; LI Dandan; CAO Shiyi (Yixue xinzhi zazhi)
Doctors' job satisfaction is an important indicators of the development of the medical and health industry which has significant effects on the quality of health services and patients' medical ex-perience. Although there are many common factors influencing doctors' job satisfaction, studies show that there are significant differences in the influencing factors between general practitioners and spe-cialists. Using the current job satisfaction situations of general practitioners and specialists in China, this review summarizes the results of recent studies on job satisfaction and analyzes the differences and similarities in factors affecting this, with the aim of proffering targeted policy suggestions for improving doctors’ job satisfaction and promoting the sound development of medical industry for hospitals and government departments.